Low emittance lattice for the storage ring of the Turkish Light Source Facility TURKAY*Supported by Turkish Republic Ministry of Development (DPT2006K120470). (June 2015) - Nergiz, Z.; Aksoy, A.
Abstract: The TAC (Turkish Accelerator Center) project aims to build an accelerator center in Turkey. The first stage of the project is to construct an Infra-Red Free Electron Laser (IR-FEL) facility. The second stage is to build a synchrotron radiation facility named TURKAY, which is a third generation synchrotron radiation light source that aims to achieve a high brilliance photon beam from a low emittance electron beam at 3 GeV. The electron beam parameters are highly dependent on the magnetic lattice of the storage ring. In this paper a low emittance storage ring for TURKAY is proposed and the beam dynamic properties of the magnetic lattice are investigated.